Characterisation Of SO2 In Off-Gas At Zimplats Smelter - L. Mabiza (The Southern African Institute of Mining and Metallurgy, 2011)
Keywords: Pyrometallurgy, furnace, sulphur, SO2, off-gas, Zimplats Zimplats embarked on an off-gas sampling campaign in December 2009 to characterise the concentration of SO2 in the off-gas from their 13 MW furnace. In excess of forty isokinetic samples (US EPA Method 8) were taken over seven days. The aim of the sampling campaign was to increase the understanding of factors that influence sulphur release from sulphide concentrates in an electric furnace. Specifically, detailed monitoring was conducted over various operating conditions to evaluate: ? The relationship between SO2 and feed rate (i.e. furnace power) ? The relationship between SO2 and ingress (i.e. furnace freeboard pressure) ? The impact of concentrate bed thickness on SO2 (i.e. blacktop) ? The effect of events such as tapping and converter slag return on SO2 ? The desulphurization reactions that take place in the blacktop A model was developed to predict the SO2 content in furnace off-gas for a particular set of operating conditions. In order to evaluate the impact of random, uncorrelated changes in concentrate composition, ingress and power (feed rate) on the SO2 content of the off-gas, a Monte Carlo approach was adopted whereby concentrate composition, power, and ingress were allowed to vary randomly around selected set-points. The model is primarily based on the release of ?labile? sulphur from the partial thermal dissociation of sulphide minerals with an over-stoichiometric sulphur content (e.g., Fe7S8 decomposition to FeS and S). The main findings of this work suggest that labile sulphur does not fully account for the measured SO2 content of the off-gas, and that limited oxidation of sulphides during melting also contributes to the SO2 content. Details of sulphide oxidation reactions in the furnace remain unclear, and it is currently not possible to provide a theoretical framework for the relationship between the extent of oxidation and variables such as temperature, gas composition, particle size, and residence time in the furnace black top. Through the use of the Monte Carlo model it was, however, possible to constrain the extent of sulphide oxidation to about 1%. This work has shown in practice what was expected in concept, that SO2 in off-gas is proportional to furnace power and ingress rate. The model that was developed consistently slightly under-predicts the quantity of SO2 generated. It also highlights that more work is required to better understand the analytical methods used to analyse for SO2 in off-gas.